Evaluating the quality of bioaerosol risk assessments for composting facilities in England and Wales - Drew, Gillian H.; Jordinson, Greg M.; Smith, Mark A.; Pollard, Simon J. T. (Elsevier Science B.V., Amsterdam., 2009)
A critical evaluation of 44 environmental risk assessments for composting facilities, submitted in support of environmental permits or exemption from licensing is presented. Assessments were scored semi-quantitatively, in triplicate, by reference to 11 generic and 11 bioaerosol-specific risk assessment attributes developed from existing regulatory guidance. Radar plots of the two attribute groups illustrate where opportunities for improvements exist, and are being used to inform regulatory guidance to the operators of composting facilities and their professional advisors. Aspects of the regulatory risk assessments requiring attention include (i) descriptions of the limitations and uncertainties within risk analyses, (ii) presentation of methodological details of sampling and analysis, and (iii) the provision of background information.
Keywords: Bioaerosols; Compost; Quality; Risk; Assessment; Regulation